2016
DOI: 10.1111/joms.12183
|View full text |Cite
|
Sign up to set email alerts
|

A Socio‐Psychological Perspective on Team Ambidexterity: The Contingency Role of Supportive Leadership Behaviours

Abstract: In addressing the notion of team ambidexterity, we propose that sociopsychological factors (i.e., team cohesion and team efficacy) may help team members to resolve paradoxical challenges and to combine exploratory and exploitative learning efforts. In addition, we theorize that senior executives may play an important role in facilitating the emergence of ambidexterity at lower hierarchical levels. In doing so, we develop a multilevel contingency framework and propose that the effectiveness of teams to achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 111 publications
(206 reference statements)
6
128
2
2
Order By: Relevance
“…A related stream of research focuses on the role of senior management in promoting ambidexterity within the whole organization rather than simply managing tensions arising between explorative and exploitative subunits. Nemanich et al (2007) explored the role of transformational leadership in promoting ambidexterity while Jansen et al (2016) argued that senior executives may play an important role in facilitating the emergence of ambidexterity at lower hierarchical levels through "the encouragement, of initiatives, the clarification of individual responsibilities, the provision of clear and complete performance evaluation feedback and the emphasis on a strong task orientation" (2016:948). Similarly, Kauppila and Tempelaar (2016) showed that employees exhibit higher ambidexterity when their group managers demonstrate a leadership style that couples strong managerial support with high performance expectations.…”
Section: Ambidexterity As a Dynamic Managerial Capability: Insights Fmentioning
confidence: 99%
“…A related stream of research focuses on the role of senior management in promoting ambidexterity within the whole organization rather than simply managing tensions arising between explorative and exploitative subunits. Nemanich et al (2007) explored the role of transformational leadership in promoting ambidexterity while Jansen et al (2016) argued that senior executives may play an important role in facilitating the emergence of ambidexterity at lower hierarchical levels through "the encouragement, of initiatives, the clarification of individual responsibilities, the provision of clear and complete performance evaluation feedback and the emphasis on a strong task orientation" (2016:948). Similarly, Kauppila and Tempelaar (2016) showed that employees exhibit higher ambidexterity when their group managers demonstrate a leadership style that couples strong managerial support with high performance expectations.…”
Section: Ambidexterity As a Dynamic Managerial Capability: Insights Fmentioning
confidence: 99%
“…On the other hand, Lechler 2001 The collective efficacy refers to the team members believing that they have the abilities and group capacity to overcome obstacles and achieve their goal(s) (Cohen and Bailey 1997). Team efficacy in the context of entrepreneurial efforts refers to how the group executes and coordinates their collective efforts to address challenges (Edmondson 1999;Arnold et al 2001;Jansen et al 2015) On the one hand, self-efficacy has been conceived as a predictor condition of entrepreneurial intentions. Drnovšek et al (2010) focus their analysis on "entrepreneurial self-efficacy", which is rooted in the individual's beliefs and motivations that support the initiative to found a business or start a business expansion processes (Krueger 1993;Drnovšek et al 2010;Tyszka et al 2011;Hattab 2014).…”
Section: Tbs Team Collaboration Capabilitiesmentioning
confidence: 99%
“…When the team holds enough cohesion and motivation both facilitate the knowledge exchange through communication and solve difficulties. Therefore, both are essential team factors where the team can deal together with unexpected problems and increase their commitment (Hoegl and Gemuenden 2001;Jansen et al 2015;Bjornali et al 2016).…”
Section: Tbs Team Collaboration Capabilitiesmentioning
confidence: 99%
See 2 more Smart Citations